Pengaruh Kualitas Produk, Citra Merek, dan Harga terhadap Keputusan Pembelian Produk Hers Protex - Dewi, Ni Putu Pasek Septiana; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research is aimed to examine the influence of product quality, brand image, and price on purchasing decisions of Hers Protex sanitary napkin products in Singaraja City. This research followed a quantitative causal design. The population consisted of consumers of Hers Protex sanitary napkin products in Singaraja City. The sampling technique used was non-probability sampling with a purposive sampling method. The sample size for this research was 97 respondents. Data were collected using a questionnaire. The data analysis technique applied was multiple linear regression. Hypothesis testing was conducted using the t-test to examine partial effects and the F-test to assess simultaneous effects, with the assistance of SPSS 26 for Windows. The results indicate that, partially, brand image and price have a positive and significant effect on purchasing decisions, while product quality has a negative effect. Simultaneously, product quality, brand image, and price have a positive and significant impact on purchasing decisions of Hers Protex sanitary napkin products in Singaraja City.